8. SEGMENTAL ANEUPLOIDIES SHOW MOSAIC PATTERN REDUCING PREDICTIVE VALUE COMPARED TO HIGH WHOLE CHROMOSOME ANEUPLOIDIES REPRESENTATIVENESS. (August 2019) - Girardi, L.; Romanelli, V.; Fabiani, M.; Cimadomo, D.; Rienzi, L.; Ubaldi, F.M.; Serdarogulları, M.; Coban, O.; Findikli, N.; Boynukalin, K.; Bahceci, M.; Patassini, C.; et al.
Abstract : Introduction: The introduction of highly sensitive Next Generation Sequencing (NGS) platforms for PGT-A applications concurred with an increased detection of segmental aneuploidies. Recent studies focused on understanding whether segmental aneuploidies derive from mitotic or meiotic events, however, definitive data are still lacking. To further contribute on the characterization of segmental aneuploidies and their biological significance, here we evaluated multifocal portions of trophectoderm (TE) tissues and Inner Cell Mass (ICM). Material & methods: Following technical validation on cell lines carrying segmental aneuploidies, a cohort study was performed between January 2018 and January 2019. After initial PGT-A analysis and genetic counselling, patients who wanted diagnostic confirmation for embryos carrying segmental aneuploidies >15Mb were enrolled. A first subset of 55 embryos carrying segmental alterations, either in concomitance (n=24) or not (n=31) with whole chromosome aneuploidies were warmed, allowed to re-expand and subjected to TE re-biopsy. An additional subset of 19 donated embryos was subjected to ICM isolation. Each biopsy was processed using Ion ReproSeq PGS kit and sequenced on Ion S5 platform. Sequencing data were blindly analyzed with Ion-Reporter software and compared with original diagnosis. Results: In the first subset of samples, regarding whole chromosome aneuploidies, comparisons between PGT-A results obtained from the first and second TE biopsy showed a concordance rate of 96.36% (n=53/55;95%CI=87.47-99.56) per sample and 99.84% (n=1263/1265;95%CI:99.43-99.98) per chromosome. Sensitivity per chromosome was 94.29% (n=33/35; 95%CI=80.84-99.30) and specificity 100% (n=1230/1230; 95%CI=99.70-100.00). Regarding segmental aneuploidies, technical validation on cell lines resulted in 100% concordance (n=12/12;95%CI=73.5-100.0). Subsequently, overall PGT-A results showed that only 53.97% (n=34/63;95%CI=40.64-66.61) of segmental alterations were confirmed in the second TE biopsy. In this group of results, 30.16% (n=19/63;95%CI=19.23-43.02) of paired samples showed the same alteration, suggesting a meiotic origin. Of the remaining results, 23.8% of the alterations (n=15/63;95%IC=13.98-36.21) showed a different aneuploidy pattern. In detail, 11.11% (n=7/63;IC95%=4.59-21.56) carried the reciprocal segmental aneuploidy of the same chromosome fragment and 12.7% (n=8/63;IC95%=5.65-23.50) showed the corresponding whole chromosome aneuploidy. These findings suggest that a percentage of TE segmental alterations are present in a mosaic constitution, consistent with mitotic origin. Discordant results, defined as the absence of any other alteration on the chromosome affected by the segmental aneuploidy, were 46.03% (n=29/63; IC95%=33.39-59.06). In the second subset of samples, considering ICM samples showing segmental aneuploidies in their corresponding clinical TE, 10 out of 19 (52.63%;95%CI:28.86-75.55) showed concordant karyotype whilst in 9 of 19 samples (47.37%;95%CI:24.45-71.14) the segmental alteration was not confirmed. Conclusions: As opposite to whole chromosome, segmental aneuploidies are not uniformly present across different blastocyst sections for a significant proportion of cases, reducing their diagnostic predictive value in IVF/PGT-A cycles. These data are important for patient counselling in cases when the embryo carries only segmental alterations; practitioners should inform patients that those embryos might be mosaic and viable. Nevertheless, the clinical value of embryos showing segmental abnormalities is still unknown and shall be evaluated in future studies. Concomitantly, the high rate of intra-blastocyst concordance observed for whole chromosome aneuploidies confirms their high clinical predictive value and diagnostic robustness of NGS for PGT-A.